Nutritious underutilized species - African baobab - Alercia, A.; Bioversity International (2013)
The African baobab is an extremely important indigenous fruit tree species for humans and animals in the dry areas of Africa. It offers shelter and provides food, fibre and medicine, as well as raw materials for many purposes. The African baobab is a neglected and underutilized species (NUS): a category of non-commodity cultivated and wild species, which are part of a large agricultural biodiversity portfolio today falling into disuse for a variety of agronomic, genetic, economic, social and cultural factors. NUS are traditionally grown by farmers in their centres of diversity, where they support nutrition security and other livelihood goals of local communities while contributing to meet their socio-cultural needs and traditional uses. Until recently these species have been largely ignored by research and development, becoming less competitive than well established major crops and losing gradually their diversity and associated traditional knowledge.